Analysis Cost 231 MultiWall Model on 4G LTE FDD 1800 and 900 Mhz Femtocell Network Planning - Alfin Hikmaturokhman; Solichah Larasati; Eka Setia Nugraha (Politeknik Negeri Semarang, 2016)
Indoor cellular network system is one solution to overcome weak signals transmited by eNodeB. Building with high cellular communication traffic levels , requiring indoor network system to maintain continuity of communication by all users. Therefore, it is necessary to plan an indoor network using Femtocell Access Point (FAP). This research is based on network design indoor propagation COST 231-Multiwall Model using the software Radiowave Propagation Simulator (RPS) and conducted at Telkom Office. The collection of data obtained is used to perform calculations on research variables include the calculation of capacity and coverage. The research showed the number of FAP for capacity and coverage is 3 FAP. The Coverage Results for scenario 2 is the best result compared with the other scenarios, with the following results, the frequency of 1800 MHz at Building 1 of -19.86 dBm, Building 2 at -21.34 dBm, and Building 3 at -28, 07 dBm. While the scenario 2 for the 900 MHz frequency in Building 1 at -13.38 dBm, Building 2 at -14.52 dBm, and building 3 of -20.39 dBm.